Impact of Plants Secondary Metabolites on White Cabbage Productivity - Borovskaia, Alla Dorofeevna; Mashcenco, Natalia Evgenievna; Ivanova, Raisa Alexseevna; Shpak, Lidia Ivanovna (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Improving the sustainability of vegetable crops to adverse growing conditions is a significant reserve for increasing yields with the already achieved level of intensification of their production. The implementation of resource-saving and especially environmentally safe technologies for the production of vegetables brings to the fore the use of biologically active substances (BASs) of natural origin as growth regulators. It is BASs with their exogenous use that can in low concentrations influence the intensity of the physiological processes in the plants, especially under unfavorable conditions for their growth. The purpose of this study was to use a complex of biologically active substances isolated from some representatives of the wild flora of Republic of Moldova (family of Plantaginaceae Juss) as growth regulators and to establish their effect on seed viability, yield and biochemical composition of white cabbage (Brassica oleracea L.). The use of the preparation Ecostim and the complex of bio-regulators from Veronica officinalis for pre-sowing seed soaking created the most favorable conditions for the growth and development of white cabbage, significantly increasing the seed germination, stimulating the processes of root formation of seedlings and its survival. The ability of these bio-regulators to improve the production process of white cabbage was established. Seed treatment with the solutions of Ecostim and complex of bio-regulators from Veronica officinalis contributed to an additional 11.1 tons and 6.7 tons of standard cabbage heads per hectare, respectively. It was shown that the pre-sowing treatment of seeds also had a positive effect on the biochemical indexes of cabbage, increasing the content of vitamin C and sugars. The performed research, its scientific and applied results allowed us to recommend the pre-sowing seed treatment with solutions of the preparation Ecostim and the complex of bio-regulators from Veronica officinalis as an element in the technology of cabbage growing.